Strategi Polri Dalam Penanggulangan Penyelundupan Narkotika Melalui Perbatasan Negara Indonesia-Timor Leste Di Kabupaten Belu - Geraldo Kevin Gebo Tomo Lawa; Jimmy Pello; Rosalind Angel Fanggi (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to analyze the strategies employed by the Indonesian National Police (Polri) in tackling narcotics smuggling across the Indonesia–Timor Leste border in Belu Regency, as well as to identify the supporting factors and obstacles in the implementation of these strategies. The research uses an empirical legal study with a qualitative approach to examine how Polri applies strategies in combating narcotics smuggling in the border area. Primary data were collected through interviews with the Head of the Narcotics Unit of Polres Belu and the Head of BNN Belu, while secondary data were obtained from literature, journals, official documents, and previous studies. Data collection techniques included interviews, observations, and document analysis. Data were analyzed using qualitative descriptive methods through coding, categorization, and interpretation, providing a comprehensive overview of the preventive, repressive, and coordinative strategies of the police, as well as the supporting and inhibiting factors in their implementation. The results indicate that Polri implements three main strategies: preventive, repressive, and coordinative. Preventive strategies include routine patrols, monitoring official and unofficial routes, and collecting information from the public and confidential informants. Repressive strategies involve investigation, arresting offenders, seizing evidence, and carrying out legal processes in accordance with applicable regulations. Coordinative strategies are implemented through inter-agency cooperation with BNN, Customs, TNI, Immigration, and Timor Leste security authorities to strengthen cross-border surveillance and law enforcement. The study also identifies supporting factors such as community participation, technological support, inter-agency synergy, and clear regulations. Conversely, obstacles include limited personnel, inadequate facilities and infrastructure, the challenging geography of the border area, potential information leaks, and coordination difficulties between agencies.